Reference intervals for hematology and biochemistry in juvenile Eastern spot-billed ducks (Anas zonorhyncha) and validation of an automated hematology analyzer for avian blood analysis - Ockju Im; Sung-Ryong Kim; Ki-Jeong Na; Kyung-Duk Min; Dong-Hyuk Jeong (PLoS ONE, 2025)
The Eastern spot-billed duck ( Anas zonorhyncha ) is a common migratory waterfowl widely distributed throughout East Asia. However, the lack of species-specific reference intervals, defined as the normal range of values derived from a healthy population for clinical interpretation, hampers accurate health assessment and clinical diagnostics in this species. This is further complicated by hematologic characteristics of avian blood, such as nucleated red blood cells and thrombocytes, which pose challenges to conventional automated measurement systems optimized for mammals. This study aimed to establish hematological and biochemical reference intervals for juvenile Eastern spot-billed ducks and to evaluate the accuracy of an automated hematology analyzer (XN-1000V, Sysmex, Japan), which newly supports avian blood analysis, compared to traditional manual counting methods. Blood samples were collected from 55 clinically healthy juvenile ducks. The established reference intervals were largely consistent with those reported in related Anas species, though Eastern spot-billed ducks exhibited a heterophil-predominant leukogram. No significant differences were observed between sexes. Comparison between manual and automated methods revealed statistically significant differences in most hematological parameters; however, most of these differences were not clinically relevant, except for thrombocyte counts. Moderate correlations were found for key parameters, including WBC, RBC, hemoglobin, PCV, and MCV, suggesting potential clinical applicability of the automated analyzer with some limitations. This study provides the first species-specific hematologic and biochemical reference intervals for juvenile Eastern spot-billed ducks under semi-captive conditions, offering valuable baseline data for clinical assessments in this subset of the population. Additionally, it highlights the need for further optimization of XN-1000V analyzers for reliable and precise application in avian diagnostics.